EFFECT OF POLYCULTURE ON THE GROWTH AND PRODUCTION OF FISH AND RICE FARMED TOGETHER - M. F. Ghazi , M. F. Ghazi; M.S.Al-Khshali , M.S.Al-Khshali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate the effect of farming of two fish species on growth traits of cultured fish and some yield components of rice crop. The field was divided into four fields planted with rice seedhing, the area of each field was 100 m², after which two species of fish were released: the common (Cyprinus carpio) and the grass carp (Ctenopharyngodon idella) in rice fields, four experimental treatments were used that were cultured with rice and fish, the first treatment included the culture of common carp alone, while the second treatment, the grass carp was cultured alone, the third treatment, The common carp and grass carp were cultured together by 50 fish each, and in the fourth treatment, the common and grass carp were cultured by 75 and 25 fish, respectively. The total weight gain and the relative, specific, and daily growth rate of the experimental fish were calculated, as well as some rice production traits. Results of the statistical analysis showed significant differences (p≤0.01) for the total weight gain and the daily, relative and specific growth rate for all treatments,T3 show asighificant differences (p≤0.01) compared to therest treatments, and the T4 showed asighificant dffercuce (p≤0.01) in compansion with T1. Results of the statistical analysis of the characteristics of the rice yield showed: as the T2 was significantly (p≤0.01) superior to osherd treatments, followed by the T4, which outperformed the T1 and T3 treatments. In the same traits, the T3 treatment outperformed the T1.